2001
DOI: 10.4049/jimmunol.166.4.2717
|View full text |Cite
|
Sign up to set email alerts
|

Brain Dendritic Cells and Macrophages/Microglia in Central Nervous System Inflammation

Abstract: Microglia subpopulations were studied in mouse experimental autoimmune encephalomyelitis and toxoplasmic encephalitis. CNS inflammation was associated with the proliferation of CD11b+ brain cells that exhibited the dendritic cell (DC) marker CD11c. These cells constituted up to 30% of the total CD11b+ brain cell population. In both diseases CD11c+ brain cells displayed the surface phenotype of myeloid DC and resided at perivascular and intraparenchymatic inflammatory sites. By lacking prominent phagocytic orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
329
0
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(349 citation statements)
references
References 53 publications
18
329
0
2
Order By: Relevance
“…28 This may reflect the fact that the central nervous system represents an immunologically challenging environment, 29,30 at least partially due to a paucity of professional APCs under normal circumstances. 31 With regard to antigen presentation in the CNS and CNS tumors, although microglia are proposed to be resident APCs in the CNS, their capability for stimulating cellular immune responses is controversial (reviewed by Carson 32 and Graeber et al 33 ). In the case of experimental autoimmune encephalomyelitis (EAE), these CD11c+ cells exhibit a maturational phenotype similar to immature BM-derived DC or splenic DCs, and were unable to prime naïve T cells, and in some cases inhibited T-cell proliferation.…”
Section: Glioma Gene Therapy With Ifn-a and Dcsmentioning
confidence: 99%
“…28 This may reflect the fact that the central nervous system represents an immunologically challenging environment, 29,30 at least partially due to a paucity of professional APCs under normal circumstances. 31 With regard to antigen presentation in the CNS and CNS tumors, although microglia are proposed to be resident APCs in the CNS, their capability for stimulating cellular immune responses is controversial (reviewed by Carson 32 and Graeber et al 33 ). In the case of experimental autoimmune encephalomyelitis (EAE), these CD11c+ cells exhibit a maturational phenotype similar to immature BM-derived DC or splenic DCs, and were unable to prime naïve T cells, and in some cases inhibited T-cell proliferation.…”
Section: Glioma Gene Therapy With Ifn-a and Dcsmentioning
confidence: 99%
“…A number of studies have shown that GM-CSF can regulate the activation of APC necessary for T cell activation and effector function [27][28][29][30]. We monitored the ability of APC to mediate the expansion of autoreactive T cells in vivo.…”
Section: Autoreactive Cd4 + and Cd8 + T Cell Experience Enhanced Expamentioning
confidence: 99%
“…59 Cells displaying immunoreactivity towards markers of dendritic cells have been observed in several experimental brain inflammatory conditions. 12,[50][51][52][53][54][55][56][57][58] In addition, the phenomenon of epitope spreading 59,60 also suggests that, once brain inflammation occurs, new antigens being released from the brain during inflammatory processes can stimulate additional immune responses. However, evidence against antigens released from the brain causing autoimmune diseases is strong, and includes the lack of autoimmunity following stroke, brain surgery, brain tumors, and brain infarcts.…”
Section: Inflammation and Adaptive Immune Responses To Adenoviral Vecmentioning
confidence: 99%
“…The presence of dendritic cells within the brain ventricles, choroid plexus, and meninges, together with lymphatics present within these structures, could represent the cellular basis for these effects. [52][53][54]56,61 Long-term transgene expression, in the presence of transitory inflammation, and in the absence of priming of either a humoral or cellular immune response, can be achieved in the brain. In other organs, this remains more difficult, since they contain, even in the resting stage, professional antigen-presenting cells with migratory properties, as well as lymphatics channels.…”
Section: Inflammation and Adaptive Immune Responses To Adenoviral Vecmentioning
confidence: 99%